Flavonoids Modulate Aspergillus flavus Proliferation and Aflatoxin Production - Lina Castano-Duque; Matthew D. Lebar; Carol Carter-Wientjes; David Ambrogio; Kanniah Rajasekaran (Journal of Fungi, 2022)
Aflatoxins are carcinogenic mycotoxins produced by Aspergillus flavus. They contaminate major food crops, particularly corn, and pose a worldwide health concern. Flavonoid production has been correlated to resistance to aflatoxin accumulation in corn. The effects of flavonoids on fungal proliferation and aflatoxin production are not well understood. In this study, we performed bioassays, fluorescence and scanning electron microscopy, and total antioxidant analysis to determine the effects of three flavonoids (apigenin, luteolin, and quercetin) on proliferation and aflatoxin production in A. flavus NRRL 3357. Results showed that concentrations of apigenin and luteolin modulated fungal proliferation and aflatoxin production in a dose-dependent manner, leading to inhibition or promotion of proliferation and toxin production. Microscopy studies of fungi exposed to flavonoids showed mycelial cell wall disruption, abnormal cell wall invaginations, and tears. Fluorescent enhancement of apigenin and luteolin using Naturstoff reagent A showed that these chemicals localized in sphere-like structures on the mycelia surface. Fungi exposed to low concentrations of apigenin, luteolin, and quercetin lowered the total antioxidant capacity in the environment compared to controls. Our results indicate that flavonoids disrupt cell wall integrity and may localize in vesicle-like structures. We hypothesize that flavonoids could act as potential signaling molecules at low concentrations and change the oxidative state of the microenvironment, either or both of which may lead to reduction of fungal proliferation and aflatoxin production.